Ethyl cellulose-based controlled-release atrazine nanoformulation for effective and long-term weed management in agriculture - Gautam, Tripurari Rao; Vasmatkar, Pashupat; Gundloori, Rathna V. N.; Kadoo, Narendra (Industrial Crops and Products, 2025)
Atrazine (ATZ) is the second most widely used herbicide. However, its widespread use is hazardous to the environment. We developed ethyl cellulose-based nanoformulated atrazine (nfATZ) to achieve slow and sustained release of ATZ for long-term weed control in crops such as maize. Maize or corn is used in several industrial applications, including the production of ethanol, corn syrup, adhesives, textiles, biodegradable plastics, etc. As broadleaf weeds significantly impact maize yields, we evaluated the effects of nfATZ and conventional ATZ on tomato as a representative of broadleaf weeds. Various concentrations of ATZ and nfATZ (1-10 mg per kg of soil) were evaluated in pre-emergence, post-emergence, and re-emergence studies. Several morphological, physiological, and biochemical parameters of weeds were assessed, and the efficacy of the herbicide formulations was evaluated. nfATZ outperformed conventional ATZ even at lower concentrations with prolonged herbicidal effectiveness beyond 30 days, while the main crop remained unaffected. The weed mortality in nfATZ treatment was > 80 %, while it was 35 % - 45 % in ATZ treatment. The chlorophyll and carotenoid contents decreased by similar to 65 % in nfATZ-treated weeds, impacting their photosynthesis and overall health. ATZ and nfATZ also significantly impacted the activities of antioxidant enzymes, such as ascorbate peroxidase (similar to 57 %), superoxide dismutase (similar to 67 %), and peroxidase (similar to 77 %) in weeds. Thus, we conclude that nfATZ performed significantly better than ATZ in controlling weeds over the long term and reducing its environmental impact. Therefore, we propose nfATZ for highly effective and long-term weed control in large-scale production of industrial crops like maize.
Keywords: Controlled-release; Herbicide; Nanoformulation; Oxidative stress; Weed management; Weed mortality

Stimulant immobilized bioactive film of functionalized egg albumin blend for wound healing - Gautam, Tripurari Rao; Patel, Pratikshkumar R.; Singam, Amarnath R.; Jagtap, Ashish S.; Desai, Prasad; Gundloori, Rathna V. N.; Pawar, Anil; Dastager, Syed G. (International Journal of Pharmaceutics, 2025)
Wound healing materials with advanced properties that facilitates higher collagen deposition, improved angiogenesis and quick tissue regeneration are crucial for clinical wound management. To meet the requirement, for the first time, our studies focus on engineering bio-originated natural materials, which are tested in combination with the active agents, ascorbic acid (AA), a stimulant and metronidazole (Mtz), an anti-microbial drug. Accordingly, a dual drug (AA, and Mtz) loaded film of functionalized egg albumin (FEA)-poly(vinyl alcohol) (PVA) was fabricated following the solution casting method. The film was characterized for its morphology and physicochemical properties using various analytical tools. The potential of the film as a wound healing material was evaluated, by in vitro drug release, degradation, cell viability, antimicrobial studies, in vivo wound healing, and histopathological analyses. In vitro degradation studies confirmed their degradability in enzymatic and soil burial conditions. Cytotoxicity studies demonstrated their non-toxicity, and the antimicrobial investigations showcased that the material was antibacterial. On the 14th day, the wound closure percentage of the wound induced control group, GI (without treatment) was notably higher at 95 % compared to the test formulation group, GV [FEA-PVA (30/70 w/w) loaded with Mtz and AA (10 % w/w of the total polymer weight), respectively], which exhibited a wound closure of 83 %. Furthermore, the histopathological examinations revealed that the inner wound healing in GV was comparatively better than in GI in terms of angiogenesis, epidermal remodeling, higher collagen deposition, coherency, and tissue regeneration. Consequently, the formulated film can be deemed a suitable wound dressing material.
Keywords: collagen; Dual drug release; Functionalized egg albumin; Polymer blend films; Stimulant; wound Healing